Technology and Developing Trends of Automatic Catwalk in China’s Drilling Rigs - Nkanza, Nilievna; Ding, Feng; Qiaolei, Sun; Yiliu, Tu (International Journal of Scientific Research and Management (IJSRM), 2018)
The Improvement of automation technology and its application in drilling rig have increased the drilling rig safety and efficiency. The petroleum drilling rig in China has been increasing as China is the fourth-leading oil producer in the oil and gas industry. However, there is a low percentage of automation equipment and the automatic catwalk still remains at the traditional stage compared to other countries. This paper introduced the present situation of the domestic well drilling rig, automatic catwalk technologies and the development trend is summarized.